Investigation of Optical and Dielectric Properties of Nickel-Doped Zinc Oxide Nanostructures Prepared via Coprecipitation Method - Sohail Ahmad; Muhammad Usman; Muhammad Hashim; Atizaz Ali; Rasool Shah; Naveed Ur Rahman (Nanomaterials and Nanotechnology)
Nanostructures of undoped zinc oxide and nickel-doped zinc oxide (Ni = Zn0.98Ni0.02O, Zn0.96Ni0.04O, and Zn0.94Ni0.06O) were synthesized by using the coprecipitation process, and their optical and dielectric properties were simultaneously investigated. The XRD results confirm the hexagonal structure having space group P63mc. By increasing nickel concentration, the particle size decreases, while the strain is increased. Fourier-transform infrared (FTIR) analysis was carried out in order to learn more about the phonon modes present in nickel-doped zinc oxide. UV-Vis spectroscopy further revealed that the optical band gap of nickel-doped samples varied from 3.18 eV to 2.80 eV. The SEM analysis confirms the rod shape morphology of the already synthesized samples. EDX analysis investigates the incorporation of nickel ions into the zinc oxide lattice. Using photoluminescence spectroscopy, we found that the synthesized materials had oxygen vacancies (Vo) and zinc interstitial (Zni) defects. Dielectric constant (εr) and dielectric loss (ε) are both improved in nickel-doped zinc oxide compared to undoped zinc oxide. Since more charge carriers enhanced after the nickel ions were exchanged for the Zn ions, the AC electrical conductivity (σa.c) improves by nickel doping compared to undoped zinc oxide.